Kajian Audit Report Lag Ditinjau dari Ukuran KAP dan Ukuran Perusahaan Subsektor Pertambangan Batu Bara - Amelia Kartika; Cindy Aryani Putri; Seniman Hati Zebua; Nasirwan, Nasirwan; Nabila Tijani Tharifah (Journal of Economic and Business Advancement, 2026)
This study examines audit report lag from the perspective of audit firm size and company size within the coal mining subsector listed on the Indonesia Stock Exchange. The research adopts a qualitative, non-empirical approach based on a systematic literature review, integrating conceptual and empirical insights to explain the determinants of audit timeliness. The findings indicate that audit firm size plays a critical role in shaping audit efficiency, where larger audit firms are associated with higher audit quality, stronger resources, and more structured methodologies that contribute to shorter audit completion periods. On the firm side, company size reflects both organizational capacity and operational complexity, creating a dual effect on audit report lag. While larger firms benefit from more sophisticated internal control systems and reporting readiness, they also face higher complexity that may extend audit procedures. The interaction between auditor characteristics and firm attributes produces a dynamic and context-dependent pattern of audit report lag.